ANALISIS PERSEPSI BMT PENGGUNA TERHADAP KUALITAS JASA PELAYANAN PPOB ABSINDO - Azfa Mutiara Ahmad Pabulo (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this research is to study the differences in expectations of service quality in the use of BMT PPOB ABSINDO by users in Yogyakarta . The research instrument is a questionnaire to the user BMT PPOB ABSINDO which includes the dimensions of service quality in general (servqual / service quality) is a system PPOB ABSINDO Payment Point to conduct payment transactions of electricity , telephon , pulses and flight tickets and train tickets in BMT users . The sample was 30 users PPOB ABSINDO BMT in Yogyakarta . Hypothesis testing is done by using gap analysis , paired sample t test , t test , and Cartesian diagram . The results of the analysis of the study found a negative gap between expectations and the reality of the quality of services PPOB ABSINDO system. The differences between expectation and reality of the quality of services that include the dimensions of service quality in general about PPOB ABSINDO described in 22 (twenty two ) perceived quality services aimed at users of PPOB ABSINDO BMT. Keywords : Quality of services , PPOB ABSINDO , Cartesian diagram